Significance of neurointervention in patients of the neuroresuscitation department - Kholliev S.S (Genius Journals, 2023)
This article discusses the importance of neurointerventional methods in patients treated in the neurocritical care unit . This year, the total number of strokes in the region is 800. A total of 115 of these patients underwent neurointerventional techniques. 75 patients with ischemic strokes had undifferentiated types of strokes, and diagnostic angiography of the carotid arteries was performed mainly as a diagnostic method.
Keywords: neurointerventional; stroke; angiography